Off‐label use of the amplatzer ductal occluder II additional size for percutaneous treatment of acute aortic occlusion in a baby. Issue 1 (5th July 2016) - Ferraro, G.; Marini, D.; Agnoletti, G.
Abstract : We describe the case of a 5‐month‐old baby with a pro‐coagulative condition, referred for rapid atrial tachycardia. At echocardiography we found a large free‐floating atrial thrombus that spontaneously embolized into the descending aorta and produced acute sub‐renal occlusion. Aorta and iliac vessels were cleared using the ADO II additional sizes device. © 2016 Wiley Periodicals, Inc.